The Influence of Enterprise Resource Planning (ERP) on PT Kimia Farma Tbk - Yulfiswandi, Yulfiswandi; Angel, Angel; Pratama, Desi; Go, Michelle; Sunaidi, Nicholas; Shirlyn, Shirlyn (Invoice : Jurnal Ilmu Akuntansi, 2024)
Kimia Farma is a company engaged in pharmaceutical health in Indonesia with subsidiaries PT Kimia Farma Apotek, PT Kimia Farma Diagnostika, PT Kimia Farma Plant, and PT Kimia Farma Trading & Distribution. Initially, in 1817, Kimia Farma company was named NV Chemicalien Handle Rathkamp & Co.. This company provides decision-making support tools as well as multi-currency and multilingual system support tools that are useful for supporting the progress of the company on an international scale. The type of research that is conducted to analyze this company is by using descriptive research. Descriptive research is a research conducted by providing a description of an event that is currently happening by giving a detailed explanation. The scope of the ERP implementation done by Kimia Farma includes license acquisition, hardware/servicer acquisition, ERP implementation service acquisition, and managed service acquisition. By increasing the services provided and adding more facilities, customers who visit or seek for treatments at Kimia Farma could get maximum service and feel more comfortable.